First principles study of lithium nitrides as anode materials for lithium rechargeable batteries - Wu, Shunnian (2013)
Lithium nitrides have emerged as promising anode materials in lithium rechargeable batteries. First principles density functional theory (DFT) methods based on plane wave basic sets and projector augmented wave have been proven to be useful tools for lithium nitride study. In this work, we employed DFT methods to study various lithium nitrides obtained from Li3N by metal and non-metal doping for potential applications as anode materials. We first investigated the electronic structure and the vacancy formation in parent Li3N using first principles methods. Li vacancy formation energy decreases with an increase of nitrogen partial pressure, while N vacancy formation energy increases with an increase of nitrogen partial pressure. The Li(2) vacancy is found to be the dominant defect with the lowest formation energy under nitrogen-rich conditions, suggesting that a nitrogen-rich condition is preferred for Li3N fabrication process for high Li ionic conductivity. We subsequently studied the effect to 3d transition metal doping on the electronic and ionic conduction of Li3N. The ionic radius of transition metal may determine its substitution site in Li3N. Ti substitution energetically favors at Li(2) site while other 3d transition metals prefer Li(1) substitutions. V, Cr, Mn, Fe, Co and Ni substitutions significantly bring down energy band gap with localized electrons at the Fermi level, suggesting introduced electronic conduction. Transition metal substitution generally reduces Li vacancy formation energy, and hence enhances the Li vacancy concentration, in particular by Sc, V and Cr. It is further revealed that transition metals except Co and Cu strongly trap the increased Li vacancies according to their dopant-vacancy binding energies, which could retard the Li ionic conduction. The reported excellent performance of Co doped Li3N as anode material is confirmed due to its improved ionic and electronic conduction. We further studied the electronic structure and bonding of transition metal M (M = Co, Ni and Cu) substituted Li3N. Co or Ni substitution can bring about mixed electronic and ionic conduction.